REKONSTRUKSI KEBIJAKAN PENGELOLAAN KAWASAN KONSERVASI BERBASIS KEARIFAN LOKAL SEBAGAI KONTRIBUSI MENUJU PENGELOLAAN SUMBER DAYA ALAM YANG INDONESIA - Negara, Purnawan Dwikora (Jurnal Konstitusi, 2011)
The management of conservation areas in Indonesia is important not due to the fact that Indonesia is a mega biodiversity country, to its close relationship with is local cultural diversity. The policy in managing the conservation areas is applied for those where the community, in terms of local wisdom, has applied the conservation values themselves. But it is the community possesing the local wisdom values that is not protected or marginalized. Viewed from the analysis of legal substance, there are some aspects that may result in why any policies on the management of conservation areas of the natural resources haven’t given any legal protection for reservation and the continuation of the functions of the natural resources: biocentrism of the management of conservation areas, too dominant roles of the government/country, no recognition and protection of access to conservation areas and rights to master and to make use of the natural resources for local people; quasi roles of the people; prerequisite to regulate the state’s rights. Phylosophically, juridically, and sociologically, local wisdoms posses important (strategic) values as a base for making policies on conservation in an unique way in Indonesia. In order to reach a policy with a local wisdom-based conservation management , legal regulations accommodating local wisdoms and bureaucrats (managers of National Parks) have bravery in positioning themselves to solve any hindrances in formal legality to create substantive justice are needed.